Photographic assessment of cephalometric measurements - Rosas Gomes, Liliane de Carvalho [UNESP]; Carpio Horta, Karla Orfelina; Gandini, Luiz Gonzaga [UNESP]; Gonçalves, Marcelo [UNESP]; Gonçalves, João Roberto [UNESP] (E H Angle Education Research Foundation, Inc, 2013)
Objective: To investigate the relationship between craniofacial measurements obtained from cephalometric radiographs and analogous measurements from profile photographs.Materials and Methods: Lateral cephalograms and standardized facial profile photographs were obtained from a sample of 123 subjects (65 girls, 58 boys; age 7-12 years). Intraclass correlation coefficients (ICCs) were calculated from repeated photographic measurements to evaluate method reliability. Analogous cephalometric and photographic measurements were compared to assess Pearson correlation coefficients. Linear regression analyses were conducted between the measurements that achieved correlation coefficients greater than r = 0.7.Results: The reliability of the photographic technique was satisfactory. Most measurements showed ICCs above 0.80 and highly significant correlations (P <= .001) with cephalometric variables. Among all measurements used, the A'N'B' angle was the most effective in explaining the variability of its analogous cephalometric, mainly for female subjects (r(2) = 0.80). The FMA' angle showed the best results for vertical assessment (r(2) = 0.65).Conclusions: The photographic method has proven to be a repeatable and reproducible tool provided that a standardized protocol is followed. Therefore, it may be considered a feasible and practical diagnostic alternative, particularly if there is a need for a low-cost and noninvasive method.
Keywords: Photography; Cephalometry; Diagnosis